USE OF APPLICATION TECHNIQUES IN ARTICAL DECORATION - Khomidov Vokhidjon Obidovich; Tursumatova Shaxlo Samievna; Xalilova Dildora (Galaxy International Interdisciplinary Research Journal, 2021)
This article discusses the use of applique in the decoration of garments in the light industry,and the types of appliqués.